GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 489799 species occurrences available in GBIF matching the query: TaxonKey: Selasphorus Swainson, 1832. The dataset includes 489799 records from 124 constituent datasets: 2 records from Ghent University - Zoology Museum - Vertebrate collection. 11 records from SUI Vertebrate Collection. 8 records from CSUC Vertebrate Collection. 14 records from Coleção de Aves do Museu Nacional / UFRJ. 310 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 2 records from Zoology (Museum of Evolution - Uppsala). 14 records from CHAS Ornithology. 3 records from Perot Museum of Nature and Science. 8 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 4 records from The avian collection at the Natural History Museum, Oslo, Norway. 3 records from UAFMC Birds. 237 records from DMNS Bird Collection (Arctos). 5 records from TTRS Ornithology. 25 records from ISM Ornithology Collection. 305 records from Field Museum of Natural History (Zoology) Bird Collection. 20 records from HSU Wildlife Eggs and Nests. 7 records from Museum Victoria provider for OZCAM. 3 records from Eggs Specimen. 63 records from CRCM Vertebrate Collection. 1 records from MVZ Hildebrand Collection (Arctos). 6 records from Ornithologie ZMK. 3 records from Lund Museum of Zoology (MZLU). 52 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 5 records from Bird Monitoring Data. 6 records from MBML-Aves - Coleção de Aves MBML. 2 records from UCM Bird Eggs/Nests Collection (Arctos). 1 records from NCSM Birds Collection. 30 records from UAM Bird Collection (Arctos). 35 records from CCBER Ornithology Collection. 689 records from Museum of Comparative Zoology, Harvard University. 408 records from CAS Ornithology (ORN). 471242 records from EOD - eBird Observation Dataset. 868 records from iNaturalist Research-grade Observations. 17 records from NYSM Birds. 10 records from Birds collection of Yamashina Institute for Ornithology. 3 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 117 records from MVZ Bird Observations (Arctos). 38 records from naturgucker. 2 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 1 records from Tissues Specimens. 3 records from Museu Paraense Emilio Goeldi - Ornithology Collection - Skin. 207 records from SBMNH Vertebrate Zoology. 393 records from LACM Vertebrate Collection. 2 records from Western Australian Museum provider for OZCAM. 62 records from SysTax - Zoological Collections. 25 records from Natural History Museum (London) Collection Specimens. 1 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 173 records from Macaulay Library Audio and Video Collection. 63 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 10 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 1 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 174 records from NatureServe Network Species Occurrence Data. 3 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 6 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 1 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 7 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 1 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 10 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 17 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 13 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 694 records from NMNH Extant Specimen and Observation Records. 1 records from Collection Ornithologie - SNSD. 4633 records from Great Backyard Bird Count. 74 records from Canadian Museum of Nature Bird Collection. 301 records from UWBM Ornithology Collection. 129 records from Royal British Columbia Museum. 17 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 221 records from LSUMZ Birds Collection. 1 records from Bird collection of National Museum of Nature and Science. 13 records from Birds Specimens. 236 records from SDNHM Birds Collection. 33 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 111 records from CNAV/Coleccion Nacional de Aves. 34 records from MMNH Museum Bird Collection. 142 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 157 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1864 records from Point Reyes Bird Observatory - Point Counts. 261 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 217 records from ORN. 12 records from Aves MZS. 4 records from Naturalis Biodiversity Center (NL) - Aves. 321 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 75 records from MZFC/Coleccion de Aves. 54 records from UCM Bird Collection (Arctos). 613 records from WFVZ Bird Collections. 122 records from PSM Vertebrates Collection. 292 records from MLZ Bird Collection (Arctos). 21 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 1 records from Biological and palaeontological collection and observation data MNHNL. 78 records from Collection Aves (spirit preserved) SMF. 1 records from Collection Aves (bird skeletons) SMF. 79 records from Collection Aves (bird skins) SMF. 86 records from UAZ Bird Collection. 667 records from AMNH Bird Collection. 59 records from HSU Wildlife Birds. 60 records from MVZ Egg and Nest Collection (Arctos). 3 records from Nest Specimen. 7 records from Collection ornithologique A. Maës. 1 records from Queensland Museum provider for OZCAM. 216 records from CM Birds Collection. 2 records from Auckland Museum Land Vertebrates Collection. 6 records from UWYMV Bird Collection (Arctos). 7 records from Geographically tagged INSDC sequences. 56 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 89 records from Cowan Tetrapod Collection - Birds. 14 records from UTEP Vertebrates. 11 records from WNMU Bird Collection (Arctos). 513 records from UMMZ Birds Collection. 131 records from DMNH Birds. 22 records from DMNS Egg Collection (Arctos). 135 records from MSB Bird Collection (Arctos). 167 records from Colección nacional de zoología. 1 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 609 records from MVZ Bird Collection (Arctos). 96 records from KUBI Ornithology Collection. 2 records from Anymals+plants - Citizen Science Data. 5 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 58 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 58 records from CUMV Bird Collection (Arctos). 2 records from South Australian Museum Australia provider for OZCAM. 133 records from LSUMZ Bird Tissues. 9 records from CHAS Oology Collection (Arctos). 9 records from Bird Collection of Museum and Institute of Zoology PAS. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences